KONTRIBUSI MINAT DALAM PENINGKATAN HASIL BELAJAR FILSAFAT PENDIDIKAN - Ramli Abdullah (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2014)
Learning  is  change of somebody ability and defensible in certain range of time. Various growth that happened in learning that, like behaviour change after student somebody getting various experience  at various situation learn the itself, so that from various that experience will cause the change process that happened in x'self of student somebody. Result learn  is entire  efficiency and its result  is which  reached for  by  student  of through   study process and specified with the number measured  by  pursuant to test  of result of learning. That result learn which  is  reached for by student after experiencing of experience learn in eye of learning  of Education Philosophy followed of. That study activity to eye of related/relevant kuliah Education Philosophy once with the enthusiasm problem, motivate and mount the dread,  so that  can succeed in learning eye of certain learning  Education Philosophy, hence student somebody shall have the enthusiasm to eye of the learning  Education Philosophy, because that enthusiasm will influence the somebody motivation to  be diligent in learning. such hence student enthusiasm in learning in this article is student enthusiasm to eye of kuliah of Education Philosophy, because student interested to a eye of learning  of Education Philosophy so that he will learn easily and please in activity of study of eye of learning  of Education Philosophy which following.